Looking for a new legitimacy: internal challenges within the Israeli Left - Daniele, G. (2016)
Considering current Israeli society in terms of the asymmetric power relations and privileges experienced by its heterogeneous population, this paper aims at questioning the role played by Israeli left-wing parties and grassroots organizations since the failure of the Oslo ‘peace process’, with a focus on the aftermath of the legislative elections of 2015. In general, most of the political initiatives led by the Zionist Left can be seen to have lost the internal legitimacy they need in order to challenge the assumptions underpinning the power asymmetries. By taking account of those narrative identities excluded from the mainstream Zionist Left discourse, among which are the Palestinian citizens of Israel, Mizrahi Jews, women’s feminist activists and African asylum seekers, I attempt to problematize the ethnic, national, class and gender cleavages emerging in a situation which includes some complex instances of dispossession and marginalization. In a settler colonial context such as the one prevailing in Israel, I question whether the left-wing has been able to represent and to support the rights of the most marginalized communities and to face up to the neo-liberal and ethno-nationalist drift which is gathering increasing momentum inside the country. Deploying an approach that is contrary to the predominant narrative, which addresses the parties and the grassroots groups of the Israeli Left as types of activism based on a single and homogeneous platform, I draw attention to alternative socio-political initiatives that have often been silenced by the mainstream, such as those initiated by radical left-wingers, ’48 Palestinians, Mizrahim, feminist activists, and also more recently by African migrants and asylum seekers. In this way, the paper also deals with the necessity of providing a means of expression for the critical points of view emerging from the most marginalized backgrounds of Israeli society, a need which is underlined by a good number of my interviewees, and a need which, if fulfilled, could enable the building up of a new and broader legitimacy within the Israeli leftist political arena.